2016
DOI: 10.11604/pamj.2016.25.238.10564
|View full text |Cite
|
Sign up to set email alerts
|

Profil épidémio-clinique des dermatoses chez les enfants vus en consultation dermatologique dans le service de dermatologie du centre national d’appui à la lutte contre la maladie à Bamako (Mali)

Abstract: IntroductionLes maladies de peau constituent un problème majeur de santé publique dans les pays en voie développement. En pratique courante les enfants représentent la couche sociale la plus touchée. Le but de notre travail était de décrire les aspects épidémio- cliniques des dermatoses chez les enfants de 0-15 ans dans le service de dermatologie du centre national d’appui à la lutte contre la maladie à Bamako, Mali.MéthodesIl s’agissait d’une étude transversale effectuée au cours de la période allant du premi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 8 publications
2
10
1
2
Order By: Relevance
“…This study provided an overview of children's skin diseases in Toamasina. The present study found that 21.90% of the patients seen in dermatology in Toamasina were children; this frequency is comparable to the results of the literature [ 1 , 2 , 5 ]. The demographic profile of these children was superimposed on that of the literature.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study provided an overview of children's skin diseases in Toamasina. The present study found that 21.90% of the patients seen in dermatology in Toamasina were children; this frequency is comparable to the results of the literature [ 1 , 2 , 5 ]. The demographic profile of these children was superimposed on that of the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were found in Côte d'Ivoire with a female predominance at 54.06% [ 3 ] and in Greece at 52.8% [ 6 ]. In Mali and India, it found a male predominance with, respectively, 55.10% and 58% [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are in line with those observed by Kourouma et al, in Ivory Coast where atopic dermatitis origin accounted for 48.8% of IADs and prurigo strophulus 12.1% [6]. For Youssouf et al, in Mali IADs represented 32.7% of all dermatoses and were dominated by atopic dermatitis (15.6%), prurigo (9.50%) [9]. The high frequency of these IADs could be explained by the fact that they are the subject of frequent consultations because they are more or less chronic dermatoses, pruritic and worrying for the parents.…”
Section: Discussionsupporting
confidence: 90%
“…Bacterial and parasitic dermatoses were followed by bacterial and parasitic dermatoses with 7.6% respectively. These results are different from those observed in Morocco with a predominance of bacterial dermatoses 56.25% and viral dermatoses 25% and similar to those observed in Mali where mycotic dermatoses were at the top of the list with a frequency of 17.2% [9,10].…”
Section: Discussioncontrasting
confidence: 67%